The relationship between state and capital: the reconstruction of soccer stadiums as an urban transformation project - Bayralı, Önsel Gürel. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
This study analyzes the relation between state and capital in Turkey to provide an account of the accumulation strategy during the AKP period (between 2002–2015) by focusing on a discernable trend in urban transformation projects, that of the reconstruction of soccer stadiums in Anatolian metropolises. In particular, this work aims to clarify the role of political entrepreneurship in the reconstruction of soccer stadiums through a partnership between state and capital. The term political entrepreneurship refers specifically to a neoliberal form of articulatory practice that serves to reproduce consent for the regeneration of the hegemony of the power-bloc. In this regard, the reproduction of hegemonic project enables the continued generation of economic imaginary in the society in such a manner that the articulation mechanism of hegemonic power and its associated regime of accumulation operate effectively and reproduces themselves.
Keywords: Stadiums -- Turkey -- Design and construction.